Targeting ferroptosis: a novel therapeutic strategy for the treatment of retinal diseases - Hao, Xiao-Dan; Xu, Wen-Hua; Zhang, Xiaoping; Xue, Junqiang (Frontiers in Pharmacology, 2024)
Ferroptosis plays a vital role in the progression of various retinal diseases. The analysis of the mechanism of retinal cell ferroptosis has brought new targeted strategies for the treatment oftreating retinal vascular diseases, retinal degeneration and retinal nerve diseases, and is also a major scientific issue in the field of ferroptosis. In this review, we summarized results from currently available in vivo and in vitro studies of multiple eye disease models, clarified the pathological role and molecular mechanism of ferroptosis in retinal diseases, summed up the existing pharmacological agents targeting ferroptosis in retinal diseases as well as highlighting where future research efforts should be directed for the application of ferroptosis targeting agents. This review indicates that ferroptosis of retinal cells areis involved in the progression of age-related/inherited macular degeneration, blue light-induced retinal degeneration, glaucoma, diabetic retinopathy, and retinal damage caused by retinal ischemia-reperfusion via multiple molecular mechanisms. Nearly 20 agents or extracts, including iron chelators and transporters, antioxidants, pharmacodynamic elements from traditional Chinese medicine, ferroptosis-related protein inhibitors, and neuroprotective agents, have a remissioning effect on retinal disease in animal models via ferroptosis inhibitinginhibition. However, just a limited number of agents have received approval or are undergoing clinical trials for conditions such as iron overload-related diseases. The application of most ferroptosis ferroptosis-targeting agents in retinal diseases is still in the preclinical stage, and there are no clinical trials yet. Future research should focus on the development of more potent ferroptosis inhibitors, improved drug properties, and ideally clinical testing related to retinal diseases.